Thorny Way to the East: Expedition to China of Adviser to the Chancellery V. F. Bratishchev in 1757 - Yu. G. Blagoder (Научный диалог)
The facts testifying to the intention of the Russian Empire in the middle of the 18th century to establish equal mutually beneficial relations with China is present-ed in the article. Fragments of archival documents (decrees, memoranda, instructions, reports, etc.) about the expedition of the courier V. F. Bratishchev are given. The main attention is paid to the analysis of documents, which provide descriptions of the long preparation of the diplomatic vis-it, negotiations of V. F. Bratishchev with Qing officials in China. The degree of informativeness of documentary sources is assessed. The documents demonstrate the serious intention of the Russian administration to resolve political and economic issues through negotiations that would allow the Russian Empire to strengthen its position in the Far East. The article notes the principles of functioning of the administrative system of the Russian Empire in the middle of the 18th century. The author of this article considers the diplomatic visit of V. F. Bratishchev to be an example of the clash between the principles of Eurocentrism, which were actively gaining positions in the policy of the Russian ruling elite, and the ideas of the inhabitants of the Middle Empire about the superiority of their own civilization, surrounded by barbarians. Studying this historical event and taking into account the diplomatic mistakes made are relevant both for historical science and modern political interstate interaction.